Transverse seismic damage mode identification of deteriorating simply-supported highway bridges. (April 2022) - Lu, Xiaoluo; Xu, Lueqin; Wei, Kai; Xu, Lihan
Abstract: The sliding of laminated rubber bearings (LRBs) and failure of shear keys observed in the Wenchuan earthquake significantly increase the span collapse risk of simply-supported highway bridges and contradict the ductile design philosophy recommended by the current design code in China. In the meantime, the seismic damage mode of bridges may also change with increasing service time due to environmental corrosion sustained by the ductile element of pier. It is well accepted that the change of bridge damage mode will cause the ineffectiveness of original seismic design. In order to identify transverse seismic damage modes of deteriorating simply-supported bridges, a five-span bridge is selected as the baseline bridge and a series of time-dependent models considering the chloride intrusion are developed. A methodology for identifying the seismic damage mode of the bridge system is proposed. Incremental dynamic analyses (IDAs) are performed to study the effects of service time and shear key capacity on seismic damage modes of the baseline bridge. To validate the results obtained from the baseline bridge, comparisons of the lifetime damage modes for several typical bridge configurations are conducted through the proposed methodology. The results indicate that with the increase of the service time of bridge, the displacement response of LRBs decreases slightly while the displacement ductility response of piers increases significantly under earthquakes, and the seismic damage mode of the bridge shows a trend of changing from displacement-oriented to strength-oriented or combined damage modes. On the other hand, the increase of shear key capacity can effectively prevent excessive girder movement but intensifies the damage level of piers under earthquakes, which is in accordance with the expectations of the ductile design philosophy. In conclusion, the combined effects of environmental corrosion and shear key capacity can significantly change the seismic damage modes of bridges along the transverse direction and thus should be considered carefully during the seismic design.